Development and standardization of a knowledge test on fertilizer best management practices in major field crops - PAVANKUMAR, KEMEKAR; REDDY, CH VENU GOPALA; BABU, K MADHU; SUHASINI, K; MEENA, A; MADHAVI, A (The Indian Journal of Agricultural Sciences, 2025)
The present study was carried out during 2023–2024 at Telangana to assess farmers’ knowledge on FBMPs in major field crops. A total of six crops i.e. paddy (Oryza sativa L.), cotton (Gossypium spp.), maize (Zea mays L.), red gram [Cajanus cajan (L.) Millsp.], soybean [Glycine max (L.) Merr.] and Bengal gram (Cicer arietinum L.) were identified as the major field crops based on the average area under cultivation in both kharif and rabi seasons from 2018–2022 in Telangana state. For each crop, one district was randomly selected from the cultivating districts, resulting in six districts. To construct the knowledge test on FBMPs in major field crops, practices were identified by the author. A knowledge test was developed covering soil testing, nutrient management, weather monitoring, synthetic fertilizers, irrigation, manure, agronomic practices, soil reclamation, equipment handling, software use, and nutrient storage. The test initially included 90 items (multiple-choice, fill-in-the-blanks, reasoning, and image identification). After expert review, 87 items met the relevancy criteria (>70% Relevancy Percentage, >0.70 Relevancy Weightage, Mean Relevancy Score ≥3). Further statistical tests (item difficulty 20–80, discrimination index 0.2–0.8, significant point biserial correlations) refined the test to 44 items. The final test demonstrated high reliability (coefficient = 0.76) and strong content validity through expert validation, ensuring comprehensive coverage of FBMPs in major field crops.